PRE-TRIAL AGAINST TIPIRING ACCORDING TO POLICE PERKAP ON TRAFFIC TIPIRING HANDLING - Samuel Rado Prakoso; Khilmatin Maulida (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Traffic violations are one type of crime that is included in the category of minor crimes (Tipiring). Minor crimes are crimes that are light or harmless. This research uses normative legal research. The data used is secondary data, secondary data in this study were collected through document studies (library research). The type of approach used is a statutory approach with analytical descriptive techniques. The results of the study show that the pretrial conducted by motorized vehicle drivers who received a ticket in the context of tipiring, was carried out in stages: submitting an application to the head of the court, the application letter was registered in a pretrial case, the head of the court directly appointed the clerk and judge, the case was examined by a single judge, rules to examine related cases, and judges make decisions no later than 7 days. Law enforcement after the pretrial for traffic violations using the law of rapid examination procedure, which is regulated in Article 211 of the Criminal Procedure Code which states "what is examined according to the examination procedure in this paragraph is a case of certain violations of road traffic laws". In addition, post-trial law enforcement against traffic violations is also regulated in Article 10 paragraph (2) of the Police Chief Regulation Number 6 of 2019 concerning Criminal Acts Investigation also states: "In terms of investigating minor crimes and traffic violations, investigative activities consist of: above: inspection; notify the defendant in writing of the day, date, time and place of the trial; submit files to court; and bring the accused together with the evidence to court.”